Analisis Komunikasi Pemasaran Dalam Membangun Brand Image Pada Kafe Own Kotabumi: Pendekatan Kualitatif - Amanah Febriyanti; Hagi Julio Salas (Universitas Medan Area, 2026)
Marketing communication is understood as a systematic process carried out by business actors to convey messages and brand values to consumers through various communication channels. This activity aims to build understanding, attract attention, and create sustainable relationships with consumers so that a positive brand perception can be formed. This research aims to examine the application of the marketing communication mix in building the Brand Image of Own Café in Kotabumi. The research employs a qualitative approach using in-depth interviews, observation, and documentation as data collection techniques. The research informants consist of the owner of Own Café as the key informant and 3 customers as supporting informants. The results indicate that Own Café implements elements of the marketing communication mix, including advertising through Instagram, sales promotion through affordable pricing, public relations through friendly service and a first anniversary event, personal selling through direct interactions, and digital-based direct marketing through GrabFood. These practices contribute to shaping Own Café’s brand image as a café with a classic concept, comfortable atmosphere, friendly service, and affordable prices.